gustimadengurah@yahoo.co.id - Ngurah, I Gusti Made; Semadi Astra, I Gde; Suastika, I Made; Parimartha, I Gde (E-Journal of Cultural Studies, 2011)
The dialogue of inter religious community members in the multiculturalcommunity of Denpasar has been beneficial to the organization of collective life. Inrelation to that, this study describes the phenomenon of cultural dialogues as an attemptto realize the idea of multiculturalism and to establish harmonious atmosphere in whichdifferences are mutually accepted and appreciated. Field qualitative method is employedin this study and the data needed were collected by the technique of observation, thetechnique of in-depth interview and documentary study. The results of the study showthat the idea of the dialogue has been based on heterogeneity, frequent conflicts andenthusiasm in establishing harmony. The policies which are referred to by the dialogueare regulated in various regulations issued by several ministers, the governor and themajor. Such policies serve as the legal umbrella of the dialogue, while the dialogicprograms are determined by the government and the Communicative Forum of InterReligious Community Members (Forum Komunikasi Antar-Umat Beragama, hereonabbreviated to FKUB). The operating techniques of how the dialogue is conducted areorganized by this forum. The dialogic fluency is motivated by the supporting factorswhich are hoped to bring much success. However, there are also some obstructions whichmay lead to failures. Attempts are made to develop it into a successful one and toavoid/eliminate its negative effects. In addition, the dialogue is also philosophically,dialectally and dynamically meaningful. Generally, the understanding of suchmeaningfulness can improve the quality of the multicultural life in Denpasar City. Itseems that the formal dialogue of inter religious community members has only beenintensively conducted by the religious leaders and the leaders of the related institutions. Ithas not been averagely conducted in the grass root level yet.